Gas Hydrate Promoters - Nashed, O. (Springer Verlag, 2020)
Clathrate hydrates are a potential technology for different applications. However, the industry requires fast hydrates formation process under moderate conditions. In this chapter, the chemical and mechanical methods are demonstrated for enhancement of kinetic hydrates formation. Special attention has been paid on the most prevailing promoters for both thermodynamic and kinetic. The mechanism and criteria of each chemical were discussed. The selectivity of the chemicals for CO2 capture was reviewed based on the available literature. Â© 2020, Springer Nature Switzerland AG.